Multiple mediating roles of physical and mental health in the effects of physical exercise on prosocial behavior in junior high school students - Liangru Guo; Liang Jiang; Huizhi Huang (Frontiers in Psychology, 2025)
ObjectiveTo examine the associations between physical exercise and prosocial behavior among junior high school students, and to explore the potential mediating roles of physical and mental health in these associations, providing insights for interventions targeting prosocial behavior.MethodsUsing data from the China Education Panel Survey 2014–2015, we analyzed 7,605 junior high school students’ self-reported measures of prosocial behavior, physical exercise, and physical and mental health. An OLS regression model was employed to assess associations, and a multiple mediation model (PROCESS Model 4 with 5,000 bootstraps) was used to test indirect effects.ResultsPhysical exercise was positively associated with prosocial behavior (β = 0.191, p < 0.001), with stronger associations observed among students with highly educated parents (β = 0.184, p < 0.001) and male students (β = 0.178, p < 0.001). Both physical health [β = 0.018, 95% CI (0.012, 0.024), p < 0.001] and mental health [β = 0.009, 95% CI (0.005, 0.013), p < 0.001] showed significant indirect associations in the link between physical exercise and prosocial behavior, with physical health accounting for over twice the indirect association of mental health.ConclusionPhysical and mental health may play mediating roles in the relationship between physical exercise and prosocial behavior among junior high school students. Schools and families should encourage students’ participation in physical exercise, which may support their physical and mental well-being and foster prosocial behavior.